Carpal joint injuries in cats – an epidemiological study - Nakladal, B.; vom Hagen, F.; Brunnberg, M.; Gross, M.; Nietz, H.; Brunnberg, L. (Veterinary and Comparative Orthopaedics and Traumatology, 2013)
Objective: Injuries of the carpal joint are rare in cats. The most common cause is a fall from a height, known as ‘high-rise syndrome’. So far, only limited data about carpal joint injuries (CJI) in cats are available. The aim of this study was to investigate the epidemiology, aetiology, location, and type of CJI in cats.Methods: Case records of cats diagnosed with CJI between 1998 and 2010 were retrospectively analysed. Data concerning signalment, history and type of CJI, accompanying systemic injuries and further orthopaedic injuries were collected.Results: During the study period, 73 cats were diagnosed with CJI (87 injured carpal joints) and the prevalence in our hospital population was 0.26% (73 out of 28,482). Cats with CJI were more likely to be presented in the period from April-October (85%, p = 0.003) compared with the rest of the year. Carpal joint injuries were caused by a fall from a height in 72.6% of the cases. Of all carpal joints, the ante-brachiocarpal joint was predominantly injured (50.6%, p = 0.001) and this was commonly caused by a fall from the fourth floor or higher (p = 0.002). The carpometacarpal joint was predominantly affected by a fall from heights up to the third floor (p = 0.004).Clinical significance: The data of this study confirm previous data with respect to time of occurrence and cause of injury. Of note, the height of the fall appears to influence the location of the injury within the carpus of cats.
Keywords: Hyperextension; high-rise syndrome; fall; height; luxation